Alumni development planning of Daar En Nisa Islamic School - Mujahidin; Nabila Nurul Fatimah; Nesia Andriana; Raqib Moslimany (At Turots: Jurnal Pendidikan Islam, 2025)
Alumni are a strategic asset in the development of educational institutions, especially amidst the challenges of globalization that demand synergy between academic quality, character, and social contribution. This article comprehensively discusses the alumni development planning of Daar En Nisa Islamic School, an Islamic educational institution for girls in Bogor that emphasizes holistic education based on faith, knowledge, and charity. This study uses a qualitative approach with library research methods to explore theories, strategies, and best practices in alumni management. Daar En Nisa implements various strategies for developing quality alumni, such as talent mapping, interest- and potential-based majors, and guidance towards State Universities (PTN). Furthermore, character building through the integration of Pancasila and Islamic values serves as a primary foundation in shaping students' personalities. This strategy produces alumni who excel not only academically but also possess spirituality, integrity, and high competitiveness. To build an active and productive alumni network, the school develops a digital communication platform, organizes mentoring programs, seminars, internships, and a digital newsletter. Alumni are also encouraged to play a role in the institution's development through intellectual, material, and spiritual contributions. The goals of the alumni program include career development, strengthening higher education networks, and lifelong learning. This study demonstrates that structured and sustainable alumni development planning provides mutual benefits for both alumni and their alma mater. Alumni become strategic partners in realizing the vision of holistic and transformative Islamic education. This article recommends that every educational institution develop an alumni development strategy as an integral part of its long-term planning, in order to create a generation of competitive learners who can make a real contribution to the community and the nation. Keyword: Planning, Development, Alumni, Islamic Education, Character